(untitled) (Applied Biological Research, 2023)
Fetal anomalies and monstrosities are the most common cause of dystocia in bovines. Fetal dystocia is a condition that occurs due to abnormal size, position or presentation of fetus resulting in difficult calving. In bovines, the incidence of dystocia is quite higher than other farm animal species (Dutt et al., 2021). Dystocia in dairy animals is responsible for unpredictable economic losses in terms of calf morbidity and mortality (Bicalho et al., 2007), impaired fertility with decreased milk production, treatment cost and dam mortality (Berry et al., 2007). The incidence of fetal monstrosities among fetal causes of dystocia in buffalo ranges from 7.9 to 12.8% (Singla and Sharma, 1992). Conjoined twins arise from a single ovum and are monozygotic and develop after the development of embryonic plate (Whitlock et al., 2008). Depending upon the fusion or non separation, the types of twins may differ viz., thoracopagus (40%), omphalopagus (33%), pygopagus (18%), cephalopagus (2%) and ischiopagus (2%) (Fernando, 1993). The present paper reports a rare case of conjoined dicephalus thoraco-omphalopagus tetrabrachius tetrapus dicaudatus monster fetus in a buffalo which was successfully delivered by cesarean section.